Heterogeneous convergence - Andrew T. Young; Matthew J. Higgins; Daniel Levy (Bar-Ilan University, Department of Economics, 2013)
We use U.S. county-level data to estimate convergence rates for 22 individual states. We find significant heterogeneity. E.g., the California estimate is 19.9 percent and the New York estimate is 3.3 percent. Convergence rates are essentially uncorrelated with income levels.
Keywords: O40; O11; O18; O51; R11; H50; H70; 330; Economic Growth; Conditional Convergence; Heterogeneity; U.S. County Level Data; Wirtschaftswachstum; Regionale Disparität; Regionale Einkommensverteilung; USA